Unspoken Emotions: The Use of Silence and Non-Verbal Devices in Harold Pinter's Plays (The International Journal of Educational Sciences and Arts, 2024)
Harold Pinter, a luminary in modern drama, is renowned for his masterful use of silence and non-verbal communication to convey the emotional and psychological states of his characters. This article explores how Pinter's distinctive pauses, ellipses, and minimalistic stage directions create a subtext that often speaks louder than the dialogue itself. By analysing key plays such as "The Birthday Party," "The Caretaker," and "The Homecoming," the study examines the strategic use of silence to build tension, highlight power dynamics, and depict isolation. Additionally, it compares Pinter's techniques with those of other influential playwrights like Samuel Beckett and Anton Chekhov, and reviews critical interpretations to provide a comprehensive understanding of Pinter's unique dramatic language. The findings underscore the profound impact of Pinter's non-verbal devices on modern theatre and their enduring relevance in contemporary drama.
Keywords: Masterful Use of Silence; Non-Verbal Communication in Drama; Strategic Pauses and Ellipses; Minimalistic Stage Directions; Subtext in Pinter's Plays; Building Tension Through Silence; Highlighting Power Dynamics; Depicting Isolation and Menace; Psychological Insight in Theatre